Fracture analysis of AA6061-graphite composite for the application of helicopter rotor blade - Saleemsab Doddamani; Chao Wang; M.JinnahSheik Mohamed; Md. Arefin Kowser (Fracture and Structural Integrity)
The main objective of the work is to study the fracture behavior of AA6061-graphite material using both experimental technique and finite element simulation by considering helicopter rotor blade as a case study. From the case study, it has been observed that the helicopter rotor blade, made of AA6061, has been failed at the threaded portion of the hole. Experimental fracture toughness is carried out using the compact tension specimens as per ASTM standard testing procedure. Modeling of compact tension specimens and the threaded portion of the bolt hole was utilized to analyze the fracture toughness using a simulation tool. From the results and the comparison, it is recommended to use AA6061-9wt% graphite material as a replacement of AA6061 in the application of main rotor blades of the helicopter